2022
DOI: 10.1186/s12955-022-01929-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the psychometric properties of the Chinese return-to-work self-efficacy questionnaire using Rasch model analysis

Abstract: Background Self-efficacy is a significant predictor of return to work and affects the confidence of survivors to return to work after illness. The Return-to-work self-efficacy (RTW-SE) questionnaire is a self-report questionnaire to assess confidence in returning to work with good reliability and validity. The aim of this study was to translate and cross-culturally adapt the RTW-SE questionnaire into Chinese and examine the psychometric properties among young and middle-aged stroke survivors us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Corr. on the acceptance range indicates that all items function in the same direction to predict the latent nature of the HELAM scale [58]. This contributes to a good level of construct validity [32].…”
Section: Item Fitmentioning
confidence: 90%
“…Corr. on the acceptance range indicates that all items function in the same direction to predict the latent nature of the HELAM scale [58]. This contributes to a good level of construct validity [32].…”
Section: Item Fitmentioning
confidence: 90%
“…The introduction of measurement tools for RTW‐SE is conducive to the development of quantitative research. Liu et al (2022) used Rasch model analysis to assess the psychometric properties of the Chinese return‐to‐work SE questionnaire and found that the RTW‐SE‐11 questionnaire can be used as a reliable and validated instrument for measuring SE to return to work in young and middle‐aged Chinese patients with stroke (Liu et al, 2022). The use of such instruments may be beneficial in the discussion of factors that promote workers to RTW in the labour market.…”
Section: Discussionmentioning
confidence: 99%
“…The gravel figure of the Chinese questionnaire.At present, the RTW research in China remains in the preliminary stage, and the majority of the studies are qualitative research. The introduction of measurement tools for RTW-SE is conducive to the development of quantitative research Liu et al (2022). used Rasch model analysis to assess the psychometric properties of the Chinese return-to-work SE questionnaire and found that the RTW-SE-11 questionnaire can be used as a reliable and validated instrument for measuring SE to return to work in young and middle-aged Chinese patients with stroke(Liu et al, 2022).…”
mentioning
confidence: 99%
“…The higher the number, the higher the position or the more capable the person. On the left side of the graph is the ability level of the participant, on the right is the difficulty level of the entry, from top to bottom, the ability of the participant decreases, and the difficulty of the questionnaire item decreases [35] .…”
Section: Item Person Mapmentioning
confidence: 99%